An investigation on test driven discrete event simulation - Asta, Shahriar; Özcan, Ender; Peer-Olaf, Siebers (2014)
This paper deals with the application of modern software development tools on simulation development. Recently, Agile Software Development (ASD) methods enjoy an increasing popularity. eXtreme Programming (XP) techniques, one of the techniques which belong to the ASD group of methods is a software development method which improves software quality and responsiveness of software projects through introducing short development cycles and a Test Driven Development (TDD) philosophy throughout the development. In this paper, we particularly pay attention to the application of the TDD by approaching simulation development from a test-first perspective. This study consists of a feasibility study of applying the TDD technique in simulation development in its various levels, say, acceptance and unit testing. Moreover, a simulation case study of a surgical ward has been considered, designed and implemented using the AnyLogic simulation toolkit. Our study differs from the mainstream in many ways. It addresses the feasibility of Test-Driven Simulation Development in Visual Interactive Modelling and Simulation (VIMS) environments as well as providing an insight into how the test-first concept can further help with the choice of components and acceptance testing.